2021
DOI: 10.1111/cns.13590
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of small non‐mammals in traumatic brain injury research: A systematic review

Abstract: Traumatic brain injury (TBI) is one of the leading causes of death and morbidity worldwide especially in industrialized countries. 1 TBI has become a major public health concern with a global prevalence that has escalated to almost 27.08 million people in 2016 as reported by the Global Burden of Diseases, Injuries, and Risk Factors (GBD) study. 2 The study also stated that about 8.1 million people were living with long-term disability caused by TBI, mainly due to falls and motor vehicle accidents. Traumatic br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 173 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…We cannot observe the effect of gender on cognition in worms, although in mammals, studies have found that gender has a greater impact on cognitive function 30,31 . Therefore, we believe that the C. elegans experiment cannot completely replace the mammalian experiment 32 . However, nematodes can be used as a bridge between cell experiments and animal experiments to verify the results of cell experiments and avoid the failure of animal experiments as much as possible.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We cannot observe the effect of gender on cognition in worms, although in mammals, studies have found that gender has a greater impact on cognitive function 30,31 . Therefore, we believe that the C. elegans experiment cannot completely replace the mammalian experiment 32 . However, nematodes can be used as a bridge between cell experiments and animal experiments to verify the results of cell experiments and avoid the failure of animal experiments as much as possible.…”
Section: Discussionmentioning
confidence: 96%
“… 30 , 31 Therefore, we believe that the C. elegans experiment cannot completely replace the mammalian experiment. 32 However, nematodes can be used as a bridge between cell experiments and animal experiments to verify the results of cell experiments and avoid the failure of animal experiments as much as possible. Considering that people who study the neurotoxicity of anesthetics seem to have neglected nematodes as a good model animal.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside the continued use of rodent models, there is a growing appreciation for non-mammal models due to their simplified physiology and cost-efficacy [49].…”
Section: Non-mammal Modelsmentioning
confidence: 99%
“…Drosophila melanogaster flies are used as an animal model that has 70% genetic overlap, a nervous system with glial cells, similar diversity of neurotransmitters, and exhibits most of the behavioural impairment displayed by humans [50]. Using Drosophila flies will augment our ability to explore TBI more efficiently for high-throughput screening of therapeutic compounds, with numerous different models of injury being developed like the omni bead ruptor model for mTBI [49].…”
Section: Non-mammal Modelsmentioning
confidence: 99%
“…Although they have provided key insight into numerous secondary injury mechanisms and therapy development ( 17–19 ), there are several limitations to the existing literature: (1) lengthy observation periods of the model organism, (2) high cost for experimentation and associated costs, (3) relatively difficult and lengthy genetic manipulations, and (4) ethical concerns regarding a large number of mammals experiencing pain and debilitating injury. For these reasons and others, over the past several decades, researchers have initiated non-mammalian models such as fruit flies ( Drosophila melanogaster; Drosophila ), nematodes ( Caenorhabditis elegans; C. elegans ), zebrafish ( Danio rerio ) and sea lampreys ( Petromyzon marinus ) to model human neurodegenerative diseases and to map the etiopathogenesis of aberrant tau formation after TBI ( 20 ). Lower-order vertebrate and invertebrate models offer important potential benefits to studying TBI-induced neurodegeneration, including shorter lifespans to study endpoints, vast genetic tools to manipulate the expression of genes of interest, high-throughput analysis to identify genetic and biochemical networks, screening techniques to identify potential therapeutics, and reduced cost.…”
Section: Introductionmentioning
confidence: 99%